Cell kinetics in flat (avillous) mucosa of the human small intestine. Issue 9 (September 1973) - Wright, Nicholas; Watson, Alexander; Morley, Adrian; Appleton, David; Marks, Janet
Abstract : A new method for the analysis of small-intestinal crypt-cell kinetics using routine peroral diagnostic biopsies is described. Untreated patients with childhood and adult coeliac disease and adults with the gluten-sensitive enteropathy of dermatitis herpetiformis were studied, together with groups of adult and childhood controls. In the classical flat avillous mucosae the increase in crypt size was found to be three-dimensional. The number of proliferating cells per crypt was shown to be markedly increased, and an even greater rise in the crypt-cell production rate was demonstrated. A significant increase in the mitotic index was also confirmed in the avillous mucosae. On the basis of these findings it is suggested that the characteristic crypt morphology in glutensensitive enteropathy can be explained as an adjustment to accommodate the expanded mass of proliferating and maturing cells necessary to support the augmented cell production rate. We may speculate that this in turn is a response to a pathologically rapid loss of cells from the mucosal surface.